Analysis of spontaneous individual case safety reports reported at adverse drug reaction monitoring centre: tertiary care teaching hospital in South India - Bhuvaneshwari, E.; Chakradhar, T.; Sravani, M. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Drugs are double edged weapons, they are used in treatment of the patients but in return can harm as well. The safety of drug prescribing has become a need of the hour topic in medicine. Safety monitoring of patients via Pharmacovigilance tool has become an integral part of pharmacotherapy. This study has been undertaken to analyze the various individual case safety reports including the Special situation cases of medicational error and over dose and to promote the reporting of adverse drug reactions (ADRs) among the healthcare professionals (HCPs). Methods: A retrospective non-interventional observational study was done for indexed period of six months at AMC-PvPI under Osmania Medical College and General Hospital. The reported individual case safety reports (ICSRs) are evaluated on basis of demographics of age and gender, seriousness criteria, outcome parameters and causality assessment of suspected drug (s) and suspected ADR/AE (s) as per the ICH guidelines and WHO causality assessment scale. Results: A total of 177 ICSRs are reported out of that 137 were ADRs, 36-medication error cases and 4-cases of over dose. The incidence of ADRs in females are high compared with males was identical. The occurrence of ADRs in adult patients (61%) was significantly higher than other age groups. Of total ADRs, most of them were with analgesics (26%) and highly reported system organ classification was CNS. Overall, 79% patients were recovered from ADRs. Conclusions: The results depicted an insight to the HCPs on the importance of monitoring and reporting of ICSRs. Our study results emphasized need to roll out a pharmacovigilance practice tool to ensure the safe use of drugs for better Pharmacotherapy and development of pharmacogenomic studies.